1995
DOI: 10.1007/bf02551308
|View full text |Cite
|
Sign up to set email alerts
|

Urinary enzyme changes in children undergoing cineangiographic evaluation using iopromid

Abstract: Nephropathy due to radiocontrast media presents with a wide spectrum of changes from reversible renal dysfunction to oliguria requiring dialysis. Nineteen patients (mean age 4.5 +/- 3.7 years) were included. Mean +/- SD values of the variables obtained before and 48 hours after angiography were the following: plasma creatinine: 0.6 +/- 0.10 and 0.6 +/- 0.16 mg/dl; endogenous creatinine clearance: 76.1 +/- 17.0 and 80.9 +/- 19.3 ml/min/1.73 m2; plasma osmolality: 279 +/- 23 and 298 +/- 39 mOsm/kg H2O; urine osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Kavukçu et al administered iopromide, in a maximum dose of 5 mL/kg with low osmolarity contrast media, to 19 children with congenital heart disease. In these patients, no significant difference was observed in the levels of serum creatinine, creatinine clearance, plasma uric acid, plasma osmolarity, urine osmolarity, fractional excretion of sodium, and urine N-acetyl-β-(D)-glucosaminidase prior to and 48 h after angiography (20). As reported by Noyan et al, in 17 cyanotic and 18 acyanotic children with congenital heart disease, nonionic low osmolarity iopamidol administration did not lead to CIN development (19).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Kavukçu et al administered iopromide, in a maximum dose of 5 mL/kg with low osmolarity contrast media, to 19 children with congenital heart disease. In these patients, no significant difference was observed in the levels of serum creatinine, creatinine clearance, plasma uric acid, plasma osmolarity, urine osmolarity, fractional excretion of sodium, and urine N-acetyl-β-(D)-glucosaminidase prior to and 48 h after angiography (20). As reported by Noyan et al, in 17 cyanotic and 18 acyanotic children with congenital heart disease, nonionic low osmolarity iopamidol administration did not lead to CIN development (19).…”
Section: Discussionmentioning
confidence: 76%
“…However, today pediatric angiography patients can be discharged within 24-48 h, with no CIN-induced mortality or morbidity being expected or reported (12). In the studies reporting postprocedural serum creatinine follow-ups in pediatric angiography patients, the patient groups were monitored for from 48 h to 2 weeks (9,12,(17)(18)(19)(20). Hirch et al regarded a 50% or greater increase in basal serum creatinine levels as significant and found that 12% their patients developed CIN (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation